1992
DOI: 10.1161/01.hyp.19.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Control of the erythrocyte free Ca2+ concentration in essential hypertension.

Abstract: Since Ca2+ ions seem to directly participate in the control of erythrocyte membrane structure and deformability and because cell Ca 2+ metabolism has been repeatedly proposed to be modified in hypertension, the intracellular calcium ion concentration (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The increased Na + -H + exchange activity might not be determined only by the hyperinsulinemic state but also by the synergic interaction with cytosolic Ca 2+ , another antiporter modulator, which has been reported to have elevated values in RBCs of hypertensive patients. 48 In summary, our studies reveal that increased Na + -H + exchange activity as measured in RBCs is present in black hypertensive subjects with insulinresistant glucose disposal. Our results also demonstrate that despite impaired insulin-mediated glucose disposal in hypertensive subjects, the cellular Na + gain via enhanced activity of Na + -H + exchange is not blunted.…”
mentioning
confidence: 56%
“…The increased Na + -H + exchange activity might not be determined only by the hyperinsulinemic state but also by the synergic interaction with cytosolic Ca 2+ , another antiporter modulator, which has been reported to have elevated values in RBCs of hypertensive patients. 48 In summary, our studies reveal that increased Na + -H + exchange activity as measured in RBCs is present in black hypertensive subjects with insulinresistant glucose disposal. Our results also demonstrate that despite impaired insulin-mediated glucose disposal in hypertensive subjects, the cellular Na + gain via enhanced activity of Na + -H + exchange is not blunted.…”
mentioning
confidence: 56%
“…32 Furthermore, it has been reported that an accumulation of calcium inside the erythrocyte may lead to changes in cytoskeletal conformation and viscoelasticity of the membrane, so the cells would become less deformable. 33,34 Another original finding of our study was the lack of difference in erythrocyte sialic acid content between normotensive and hypertensive subjects, whereas hypercholesterolemia was associated with decreased erythrocyte sialic acid content in both normotensive and hypertensive groups compared with subjects with low cholesterol. The observation of similar levels of membrane sialic acid content in both hypertensive and normotensive groups was in good agreement with the literature data reporting that total sialic acid content in erythrocyte membrane did not differ between normotensive patients and those with essential or renal hypertension.…”
Section: Hadengue Et Al August 1998mentioning
confidence: 75%
“…38 Moreover, absolute peripheral blood flow is reduced in human hypertension 39 because of high blood viscosity 40 and abnormal erythrocyte rheology, such as reduced membrane fluidity, 41 and an elevated erythrocyte free Ca 2+ concentration. 42 This line of evidence implies that circulating erythrocytes of hypertensive patients experience persistent inflammatory damage and shear stress, which impairs erythrocyte filterability by signal transduction involving intracellular Ca 2+ . This can affect the blood's rheologic properties and the interaction of erythrocytes and resistance vessels, contributing to the elevation in flow resistance and BP.…”
Section: Discussionmentioning
confidence: 99%